Proceedings of the 2nd Workshop on Many-Task Computing on Grids and Supercomputers 2009
DOI: 10.1145/1646468.1646473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating use of data flow systems for large graph analysis

Abstract: Large graph analysis has become increasingly important and is widely used in many applications such as web mining, social network analysis, biology, and information retrieval. The usually high computational complexity of the commonly-used graph algorithms and large volume of data frequently encountered in these applications, however, make scalable graph analysis a non-trivial task.Recently, more and more of these graph algorithms are implemented as dataflow applications, where many tasks perform assigned opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…On the other hand, new complete languages such as X10 [29], ECL [33], UPC [21], Legion [3], and Chapel [4] have been defined by exploiting in them a data-centric approach. Furthermore, new APIs based on a revolutionary approach, such as GA [20] and SHMEM [19], have been implemented according to a library-based model.…”
Section: Exascale Programming Systemsmentioning
confidence: 99%
“…On the other hand, new complete languages such as X10 [29], ECL [33], UPC [21], Legion [3], and Chapel [4] have been defined by exploiting in them a data-centric approach. Furthermore, new APIs based on a revolutionary approach, such as GA [20] and SHMEM [19], have been implemented according to a library-based model.…”
Section: Exascale Programming Systemsmentioning
confidence: 99%
“…Our work shares with Pregel the ideal that graph processing middlewares should: (i) be useable on today's clusters or cloud computing facilities -what excludes works using massively parallel shared memory architectures [15,14] or specialized systems such as IBM's BlueGene/L [21]; (ii) provide a convenient and easy abstraction for defining a graph processing application -what excludes approaches such as using MapReduce for graph processing [3] or other existing distributed processing frameworks [7] or databases [22]; (iii) be able to distribute the cost of storing and executing an algorithm in a large graph -what excludes single-node approaches for graph processing simply by the fact that they do not provide enough primary or even secondary memory for storing and retrieving said graphs [14].…”
Section: Related Workmentioning
confidence: 99%
“…LexisNexis performed at levels in between the SQL and Hadoop systems and offered the most flexible means of specifying dataflow computations. Other researchers have reported that LexisNexis offers exceptional speedups in graph analysis algorithms [19]. Finally, Hadoop clusters can deliver excellent performance in brute-force applications, provide high-levels of fault tolerance, and are highly accessible to researchers.…”
Section: Chapter 8 Conclusionmentioning
confidence: 99%